KOMUNIKASI INTERPERSONAL DALAM MENGATASI TOXIC RELATIONSHIP PASANGAN DEWASA AWAL YANG MENJALANI HUBUNGAN ROMANTIS - KUMALASARI, LINDA; Ranteallo, Ikma Citra; Nugroho, Wahyu Budi (JURNAL ILMIAH SOSIOLOGI: SOROT; Vol 5 No 1 (2025): JISSOROT, 2025)
This study focuses on resolving toxic relationships. Toxic relationships can be interpreted as unhealthy relationships. This study used early adult informants aged 19-24 years. The aim is to determine the role of interpersonal communication in overcoming toxic relationships in early adult couples who are in romantic relationships. In addition, the method used in this study is a qualitative research method using primary and secondary data sources, and using data collection methods by interviewing and documentation then analyzed with data reduction, presentation, and drawing conclusions. The results of this study found that communication is an important key in living a relationship because lack of communication can result in a toxic relationship. This study found that open communication, full of empathy, supportive, positive 2 attitudes, and equality. can overcome the occurrence of toxic relationships. The theory used is relational maintenance by Laura Stafford and Daniel J. Canary. In this study, it was found that there is an importance of a relationship maintenance strategy so that the relationship continues to run stably, namely, 1) Positive attitude, providing comfort, emotional support and spending time with a partner. 2) Openness, being honest and open to each other both in feelings and problems that occur in the relationship. 3) Assurance, with commitment and assurance in undergoing a relationship makes the relationship more focused. 4) Network, this network is more directed at relationships such as family environment, friendship and play environment that have positive characteristics. 5) Division of tasks, couples will divide tasks fairly, both have the same rights and obligations to establish a relationship together. So it can be concluded that the existence of interpersonal communication and the existence of relationship maintenance strategies in couples are important factors in resolving toxic relationship problems so that the relationship can survive these problems.